Analytical evaluation of QuantiFERON- Plus and QuantiFERON- Gold In-tube assays in subjects with or without tuberculosis. (September 2017) - Petruccioli, E.; Vanini, V.; Chiacchio, T.; Cuzzi, G.; Cirillo, D.M.; Palmieri, F.; Ippolito, G.; Goletti, D.
Abstract: The QuantiFERON-TB Gold Plus (QFT-Plus) represents the new QuantiFERON-TB Gold In-tube (QFT-GIT) to identify latent tuberculosis infection (LTBI). The main differences is the addition of a new tube containing shorter peptides stimulating CD8 T-cells. Aim of this study is to evaluate the accuracy of QFT-Plus compared with QFT-GIT in a cross sectional study of individuals with or without tuberculosis (TB). We enrolled 179 participants: 19 healthy donors, 58 LTBI, 33 cured TB and 69 active TB. QFT-Plus and QFT-GIT were performed. The two tests showed a substantial agreement. Moreover we found a similar sensitivity in active TB and same specificity in healthy donors. A higher proportion of the LTBI subjects responded to both TB1 and TB2 compared to those with active TB (97% vs 81%). Moreover, a selective response to TB2 was associated with active TB (9%) and with a severe TB disease, suggesting that TB2 stimulation induces a CD8 T-cell response in absence of a CD4-response. In conclusion, QFT-Plus and QFT-GIT assays showed a substantial agreement and similar accuracy for active TB detection. Interestingly, a higher proportion of the LTBI subjects responded concomitantly to TB1 and TB2 compared to those with active TB, whereas a selective TB2 response associated with active TB.